2009
DOI: 10.1016/j.exer.2008.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells in the trabecular meshwork: Present and future promises

Abstract: Primary open-angle glaucoma is recognized as a disease of aging, and studies show a relationship between aging and trabecular meshwork (TM) cell density. Human TM cell division occurs primarily in the anterior, non-filtering region. A commonly used glaucoma treatment, laser trabeculoplasty (LTP), triggers and increases cell division, as well as cell migration of these anterior TM cells. These freshly-divided migrating cells repopulate the burned laser sites, suggesting that they are stem cells. Several studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
80
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 61 publications
5
80
0
1
Order By: Relevance
“…In the normal eye, resident endothelial cells of the TM maintain its structure by continuously remodeling the TM beams and by degrading debris that might otherwise accumulate and occlude the outflow pathways. Loss of TM cells has been suspected to contribute to aqueous humor outflow deficiencies and, conversely, it has been hypothesized that replacing lost cells can restore function to the eye (39). Previous studies by this and other laboratories have indicated that either multipotent cells isolated from the TM (40,41) or iPSC may be useful for this purpose (23,42).…”
Section: Discussionmentioning
confidence: 99%
“…In the normal eye, resident endothelial cells of the TM maintain its structure by continuously remodeling the TM beams and by degrading debris that might otherwise accumulate and occlude the outflow pathways. Loss of TM cells has been suspected to contribute to aqueous humor outflow deficiencies and, conversely, it has been hypothesized that replacing lost cells can restore function to the eye (39). Previous studies by this and other laboratories have indicated that either multipotent cells isolated from the TM (40,41) or iPSC may be useful for this purpose (23,42).…”
Section: Discussionmentioning
confidence: 99%
“…They also expressed AnkG, a putative marker for PET cells [13][14][15]. On the contrary, the primary cells only expressed Pax6.…”
Section: Discussionmentioning
confidence: 99%
“…Kelley et al [14] reported exclusive immunostaining of AnkG and BA46 in the human TM insert cells post-laser trabeculoplasty in an organ culture model. Cultured human TM insert cells were found to express BA46 [15]. It was speculated that the Schwalbe's line cells, novel cells, and TM insert cells may be one and the same and represent the putative stem cells in the transition zone at the posterior limbus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, reduced TM cellularity is significantly associated with OAG [14]. Although no experimental evidence that this TM cell loss is physiologically significant has been presented previously, it has been assumed that this would compromise outflow pathway function, that is, IOP regulation [15]. OAG is a disease of aging, with incidence increasing after 40, and the outflow pathway is subjected to numerous cellular insults.…”
Section: Introductionmentioning
confidence: 99%